2019
DOI: 10.1001/jama.2019.7233
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative Accuracy of FEV1:FVC Thresholds for COPD-Related Hospitalization and Mortality

Abstract: IMPORTANCE According to numerous current guidelines, the diagnosis of chronic obstructive pulmonary disease (COPD) requires a ratio of the forced expiratory volume in the first second to the forced vital capacity (FEV 1 :FVC) of less than 0.70, yet this fixed threshold is based on expert opinion and remains controversial. OBJECTIVE To determine the discriminative accuracy of various FEV 1 :FVC fixed thresholds for predicting COPD-related hospitalization and mortality. DESIGN, SETTING, AND PARTICIPANTS The Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
1
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(125 citation statements)
references
References 48 publications
3
113
1
8
Order By: Relevance
“…We acknowledge that the fixed threshold FEV1/FVC < 0.7 diagnostic criterion for COPD endorsed by Global Initiative for Chronic Obstructive Lung Disease(GOLD) may have also misclassified individuals with obstructive lung disease as PRISm. In a recent large population-based sample (n = 24,207), Bhatt and colleagues showed that the discriminative accuracy of FEV 1 /FVC < 0.7 to predict COPD-related death and/or hospitalization was not inferior to FEV 1 /FVC < LLN 36 . We assert that because the majority of our findings remained robust on sensitivity analyses using LLN-defined lung function categories.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that the fixed threshold FEV1/FVC < 0.7 diagnostic criterion for COPD endorsed by Global Initiative for Chronic Obstructive Lung Disease(GOLD) may have also misclassified individuals with obstructive lung disease as PRISm. In a recent large population-based sample (n = 24,207), Bhatt and colleagues showed that the discriminative accuracy of FEV 1 /FVC < 0.7 to predict COPD-related death and/or hospitalization was not inferior to FEV 1 /FVC < LLN 36 . We assert that because the majority of our findings remained robust on sensitivity analyses using LLN-defined lung function categories.…”
Section: Discussionmentioning
confidence: 99%
“…Research using hospital administrative data or fixed cutoffs for spirometric indices introduces biases and risk of misclassification of COPD, although this topic remains controversial. [32][33][34] Use of statistically valid LLN for lung function measures, along with prior probability of disease, clinical signs, and symptoms reduces the risk of both false positives and false negatives. Using the LLN rather than 0.70 in younger adults with symptoms of airway obstruction (eg, asthma) also avoids false-negative interpretations when the LLN is above the fixed threshold.…”
Section: Not All Approaches Are Equalmentioning
confidence: 99%
“…Recent results support the use of fixed ratio less than 0.70 as appropriate to identify individuals at risk of clinically significant COPD. 5,6 However, more than a single postbronchodilator spirometric assessment may be necessary for diagnosing COPD for patients with mild airway obstruction at baseline. 7 We suggest post-bronchodilator FEV 1 /FVC ratio should be confirmed by a repeat spirometry on a separate occasion if the value is between 0.6 and 0.8, because the ratio may change as a result of biological variation.…”
Section: Introductionmentioning
confidence: 99%